EFFECT OF MENTAL HEALTH PROMOTION PROGRAM ON SOCIAL MEDIA ADDICTION AMONG UNIVERSITY STUDENTS - เชื้อประเสริฐศักดิ์ พณัฐ; วุฒิ ชูประดิษฐ์ ปริยานุช; ชูประดิษฐ์ ผศ.ดร.สุภัทร (Thai Interdisciplinary and Sustainability Review, 2023)
The aim of this study was to study the effect of a mental health promotion program on depression, anxiety, stress, loneliness, and social media addiction among university students. The purposive sampling was used to select students who were studying for a bachelor’s degree, the academic year 2022, University of Phayao. The mental health promotion program was developed by using cognitive behavioral therapy-based psychoeducation group for social media addiction and mental health problems. The total period of the program was 2 days, 10 activities, 60 minutes each. This study was measured before and after the experiment by using a general information questionnaire, the Social Media Addiction Test (S-MAT), the Depression Anxiety Stress Scale (DASS-21) and the 6 Items Revised UCLA Loneliness Scale (RULS-6) as a pretest-posttest. The result shows the mean scores of anxieties, stress, and social media addiction after receiving the mental health promotion program were significantly lower than that before at < .050. This study suggests that a program that focuses on cognitive behavioral therapy-based psychoeducation group for social media addiction and mental health problems can reduce anxiety, stress, and social media addiction among university students.